Analisis Hukum terhadap Surat Keputusan Menteri Energi dan Sumber Daya Mineral dalam Perizinan Panas Bumi - Fariz Azka Abdullah (Program Studi Ilmu Hukum, Universitas Kuningan, 2025)
This study examines the discrepancy between the Decree of the Minister of Energy and Mineral Resources (ESDM) and the applicable laws and regulations regarding the management of the Dieng and Patuha Geothermal Working Areas (WKP). The main focus of the study is the analysis of the Decree of the Minister of Energy and Mineral Resources that regulates geothermal management in the area, which is considered inconsistent with the provisions of Law No. 27 of 2003 concerning Geothermal Energy and its derivative regulations. The results of the study indicate that both Decrees of the Minister of Energy and Mineral Resources No. 2789 K/30/MEM/2012 and No. 2192K/30/MEM/2014 regulate the management of the Dieng and Patuha WKP without considering the correct licensing procedures, especially regarding the auction mechanism and permit allocation which should be carried out in accordance with Law No. 27 of 2003. This discrepancy has the potential to create legal uncertainty in geothermal management, which can hinder the development of the geothermal industry in Indonesia. This study uses a normative juridical research method with an analytical approach to the legal norms contained in Law No. 27 of 2003 and the Decree of the Minister of Energy and Mineral Resources. The data used consist of primary legal materials such as laws and decrees of the Minister of Energy and Mineral Resources, as well as secondary legal materials in the form of books, journals, and expert opinions. This study recommends the need for improvements in the issuance of the Decree of the Minister of Energy and Mineral Resources to align with existing laws and regulations, to ensure legal certainty and sustainable management of geothermal resources in Indonesia.